DO SERUM ACUTE PHASE REACTANTS PREDICT CLINICAL OUTCOME IN EMERGENCY GENERAL SURGICAL ADMISSIONS? - Khan, Saad Ullah; Soh, Jun Yi; Peleki, Aikaterini; Abdullah, Muhammad; Zaman, Shafquat; Waterland, Peter William (Journal of Ayub Medical College Abbottabad, 2018)
Background: Identifying general surgical patients at risk of poor outcome can be a diagnostic challenge. This study aimed to determine the significance of admission serum acute phase reactants in predicting emergency general surgical outcome. Methods: An electronic database containing all acute general surgical admissions over two years was analysed to correlate admission acute phase reactants (including C-reactive protein (CRP), absolute neutrophil count (ANC) and serum albumin) with outcome. Study endpoints included: cross-sectional imaging, surgery, intensive care admission, in-hospital mortality and length-of-stay (LOS). Results: A total of 9738 patients were enrolled in the study. Elevated CRP (n= 4635; 47%) was associated with: advanced imaging 17% vs 30% (p=0.0001), surgery 15% vs 28% (p=0.0001), ITU admission 3% vs 7% (p=0.0001) and mortality 0.5% vs 2% (p=0.0001). A cut-off level of >150 mg/L was most significant. Abnormal ANC (n= 4104; 42%) was significant in predicting advanced imaging 15% vs 55% (p=0.0001), surgery 17% vs 27% (p=0.0001), and ITU admission 3% vs 8% (p=0.0001). Hypoalbuminaemia (n= 1392; 14%) was associated with a 12-fold rise in mortality 0.5% vs 6%. Normal CRP, ANC with hypoalbuminaemia was a strong negative predictor of mortality (0.015% vs 1.24%), while an abnormal combination was associated with mortality of 8%. Conclusion: Admission acute phase reactants are useful to enhance acute surgical patient stratification during clinical decision making. An admission CRP above 150 should alert the clinician of a potentially high-risk patient who may require prompt intervention. A combination of abnormal results has the highest in-hospital mortality. Keywords: General surgery; C-reactive protein; Serum albumin; Neutrophils; Acute abdomen; Emergency Treatment